2020
DOI: 10.1097/dcr.0000000000001574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Factors Associated With Complications After Crohn’s Ileocolectomy

Abstract: BACKGROUND: Ileocolectomy is the most common surgery performed for Crohn’s disease, and postoperative complications occur frequently. There has been minimal evaluation of complications after ileocolectomy as a function of both clinical and genetic factors. OBJECTIVE: The purpose of this study was to evaluate both genetic and clinical factors associated with complications after Crohn’s ileocolectomy. DESIGN: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…One study by Giudici et al also investigating NOD2 polymorphisms rs2066844, rs2066845, and rs2066847 in CD patients undergoing abdominal surgery in general could not identify homozygosity as risk factor for postoperative complications but a longer time period for disease onset in the p.Leu1007fsX1008 (rs2066847) cohort [19], whereas a study by Geramain et al found the NOD2 SNP rs5743289 to be an independent risk factor for postoperative abdominal septic complications [20]. A third study by Kline et al assessed the impact of NOD2 SNPs rs2076756, Arg702Trp (rs2066844), and p.Gly908Arg (rs2066845) [21]. In our cohort, rs2076756 was not assessed and the others were quite rare with only one homozygote Arg702Trp (rs2066844) and one p.Gly908Arg (rs2066845), respectively, but Kline et al also did not find one of the NOD2 SNPs to be associated with postoperative complications after ileocecal resection [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Giudici et al also investigating NOD2 polymorphisms rs2066844, rs2066845, and rs2066847 in CD patients undergoing abdominal surgery in general could not identify homozygosity as risk factor for postoperative complications but a longer time period for disease onset in the p.Leu1007fsX1008 (rs2066847) cohort [19], whereas a study by Geramain et al found the NOD2 SNP rs5743289 to be an independent risk factor for postoperative abdominal septic complications [20]. A third study by Kline et al assessed the impact of NOD2 SNPs rs2076756, Arg702Trp (rs2066844), and p.Gly908Arg (rs2066845) [21]. In our cohort, rs2076756 was not assessed and the others were quite rare with only one homozygote Arg702Trp (rs2066844) and one p.Gly908Arg (rs2066845), respectively, but Kline et al also did not find one of the NOD2 SNPs to be associated with postoperative complications after ileocecal resection [21].…”
Section: Discussionmentioning
confidence: 99%
“…A third study by Kline et al assessed the impact of NOD2 SNPs rs2076756, Arg702Trp (rs2066844), and p.Gly908Arg (rs2066845) [21]. In our cohort, rs2076756 was not assessed and the others were quite rare with only one homozygote Arg702Trp (rs2066844) and one p.Gly908Arg (rs2066845), respectively, but Kline et al also did not find one of the NOD2 SNPs to be associated with postoperative complications after ileocecal resection [21]. In our follow-up data, we could not detect significant differences in the need for further surgical therapy or increased need for immunosuppressive or immune-modulatory therapy over time regarding the risk factors identified by others [18][19][20]: homozygous NOD2 variant, smoking, or fistulating disease.…”
Section: Discussionmentioning
confidence: 99%
“…In IBD, surgery is indicated for clinical intractability, complications, and neoplasms, and is considered an option in CD patients with isolated ileal disease[ 4 ]. Postoperative complications are frequent in IBD, especially intra-abdominal sepsis, surgical site infection (SSI), and adynamic ileum[ 5 - 9 ]. Increased understanding of the effects of nutritional status on surgical outcomes and the patient characteristics that are predictive of surgery-associated complications are essential for prompt implementation of adequate nutritional interventions[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 original clinical and scientific research articles have been published using these specimens. These publications have been the result of work with more than 30 collaborating scientists and relate to the genetics and pathophysiology diverticulitis, 31,32 the genetic basis of IBD, 33,34 disease phenotype/ genotype correlations, [35][36][37] mucus defense, 38,39 bowel permeability and myofibroblast function in IBD, [40][41][42][43] and colorectal cancer. 44,45…”
Section: The Hmc Carlino Family Ibcrd Biobank History and Settingmentioning
confidence: 99%